A replication competent luciferase-secreting DENV2 reporter for sero-epidemiological surveillance of neutralizing and enhancing antibodies - Saipin K. (2023)
Dengue virus (DENV) specific neutralizing and enhancing antibodies play crucial roles in dengue disease prevention and pathogenesis. DENV reporters are gaining popularity in the evaluation of these antibodies; their accessibility and acceptance may improve with more efficient production systems and indications of their antigenic equivalence to the wild-type virus. This study aimed to generate a replication competent luciferase-secreting DENV reporter (LucDENV2) and evaluate its feasibility in neutralizing and infection-enhancing antibody assays in comparison with wild-type DENV2, strain 16681, and a luciferase-secreting, single-round infectious DENV2 reporter (LucSIP). LucDENV2 replicated to similarly high levels as that of the parent 16681 virus in a commonly used mosquito cell line. LucDENV2 was neutralized in an antibody concentration-dependent manner by a monoclonal antibody specific to the flavivirus fusion loop and two antibodies specific to the E domain III, which closely resembled the neutralization patterns employing the LucSIP and wild-type DENV2. Parallel analysis of LucDENV2 and wild-type DENV2 revealed good agreement between the luciferase-based and focus-based neutralization and enhancement assays in a 96-well microplate format when employed against a set of clinical sera, suggesting comparable antigenic properties of LucDENV2 with those of the parent virus. The high-titer, replication competent, luciferase-secreting DENV reporter presented here should be a useful tool for fast and reliable quantitation of neutralizing and infection-enhancing antibodies in populations living in DENV-endemic areas.